Accumulation of 3-deoxyanthocyanidin phytoalexins luteolinidin and apigeninidin in sugarcane in relation to red rot disease - P. PADMANABAN and K.C. ALEXANDER, R. VISWANATHAN, D. MOHANRAJ (Indian Phytopathology, 2002)
The red pigment produced in sugarcane infected by red rot caused by Colletotrichum falcatum [Glomerella tucumanensis] was investigated. HPLC detected 3-deoxyanthocyanidin flavonoids luteolinidin and apigeninidin in diseased tissues. It is suggested that these substances may be phytoalexins of sugarcane.